'Candidatus Sarmatiella mevalonica' endosymbiont of the ciliate Paramecium provides insights on evolutionary plasticity among Rickettsiales. (26th January 2021) - Castelli, Michele; Lanzoni, Olivia; Nardi, Tiago; Lometto, Stefano; Modeo, Letizia; Potekhin, Alexey; Sassera, Davide; Petroni, Giulio
Summary: Members of the bacterial order Rickettsiales are obligatorily associated with a wide range of eukaryotic hosts. Their evolutionary trajectories, in particular concerning the origin of shared or differential traits among distant sub‐lineages, are still poorly understood. Here, we characterized a novel Rickettsiales bacterium associated with the ciliate Paramecium tredecaurelia and phylogenetically related to the Rickettsia genus. Its genome encodes significant lineage‐specific features, chiefly the mevalonate pathway gene repertoire, involved in isoprenoid precursor biosynthesis. Not only this pathway has never been described in Rickettsiales, it also is very rare among bacteria, though typical in eukaryotes, thus likely representing a horizontally acquired trait. The presence of these genes could enable an efficient exploitation of host‐derived intermediates for isoprenoid synthesis. Moreover, we hypothesize the reversed reactions could have replaced canonical pathways for producing acetyl‐CoA, essential for phospholipid biosynthesis. Additionally, we detected phylogenetically unrelated mevalonate pathway genes in metagenome‐derived Rickettsiales sequences, likely indicating evolutionary convergent effects of independent horizontal gene transfer events. Accordingly, convergence, involving both gene acquisitions and losses, is highlighted as a relevant evolutionary phenomenon in Rickettsiales, possibly favoured by plasticity and comparable lifestyles, representing a potentially hidden origin of other more nuanced similarities among sub‐lineages.